2016
DOI: 10.7554/elife.10094
|View full text |Cite
|
Sign up to set email alerts
|

Extracting grid cell characteristics from place cell inputs using non-negative principal component analysis

Abstract: Many recent models study the downstream projection from grid cells to place cells, while recent data have pointed out the importance of the feedback projection. We thus asked how grid cells are affected by the nature of the input from the place cells. We propose a single-layer neural network with feedforward weights connecting place-like input cells to grid cell outputs. Place-to-grid weights are learned via a generalized Hebbian rule. The architecture of this network highly resembles neural networks used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
198
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(210 citation statements)
references
References 46 publications
8
198
0
Order By: Relevance
“…Also note that the smallest grid scales in our model are obtained with negative-mean temporal filters (Fig 4). Yet our results agree with the ones of Dordek et al [65] in that the non-linearity introduced by imposing non-negative synaptic weights is sufficient for a triangular symmetry to emerge.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Also note that the smallest grid scales in our model are obtained with negative-mean temporal filters (Fig 4). Yet our results agree with the ones of Dordek et al [65] in that the non-linearity introduced by imposing non-negative synaptic weights is sufficient for a triangular symmetry to emerge.…”
Section: Discussionsupporting
confidence: 92%
“…The authors discuss that such a zero-mean constraint could originate either from lateral inhibition or from a zero-mean temporal filter controlling the output activity of the neuron. In the latter case, the model by Dordek et al [65] is analogous to the present one. We note, however, that effectively zero-mean inputs are neither necessary nor sufficient for grid patterns to emerge.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The exact source of positional information and thus the relationship between place cells and grid cells is still unknown, however there is physiological evidence supporting interactions between the two populations of spatial cells (Witter and Amaral, 2004; Langston et al, 2010; Wills et al, 2010; Bonnevie et al, 2013). How grid cells might rely on place cells and vice versa , is still not clear (Bush et al, 2014; Dordek et al, 2016). …”
Section: Hippocampal Formation and Related Circuitsmentioning
confidence: 99%
“…2 | GRID CODING AS AN UNDERLYING REPRESENTATIONAL METRIC OF SPACE: THE NAVIGATIONAL AND EXTENDED PERSPECTIVES As a rat navigates an environment, often by being offered rewards for exploring the environment as comprehensively as possible, grid cells fire in a relatively evenly spaced manner that covers much of the environment much like a piece of graph paper (Hafting et al, 2005;Sargolini et al, 2006). One of the key features of grid cells is that the grid often shows sixfold symmetry; in other words, the lattice surrounding each "node" in the grid forms a hexagon (Doeller, Barry, & Burgess, 2010;Dordek, Soudry, Meir, & Derdikman, 2016). Some studies have also found evidence that grid coding extends to other scales of neural recordings, such as functional magnetic resonance imaging, intracranial EEG, and MEG recordings (Doeller et al, 2010;Julian, Keinath, Frazzetta, & Epstein, 2018;Kunz et al, 2015;Maidenbaum, Miller, Stein, & Jacobs, 2018;Stangl et al, 2018;Staudigl et al, 2018).…”
mentioning
confidence: 99%